Multicompetence in L2 Language Play: A Longitudinal Case Study. Issue 1 (24th December 2013) - Bell, Nancy; Skalicky, Stephen; Salsbury, Tom
<x xml:space="preserve">Abstract</x> Humor and language play have been recognized as important aspects of second language (L2) development. Qualitative studies that have documented the forms and functions of language play for adult and child L2 users have taken place largely in classroom settings. In order to gain a fuller understanding of such creative manipulations by L2 users, it is necessary to examine these phenomena across a variety of contexts. In this article, we explore the ways that two L2 users marshal resources to play with language across communicative activities, for various purposes, and with a variety of interlocutors in interaction. Our goal is to gain a fuller view of our participants as multicompetent language users, specifically with respect to their playful communicative repertoires. The data consist of informal conversations which were recorded approximately every 2 weeks over 10–12 months. Episodes framed by the participants as playful were identified across all recordings and were analyzed qualitatively to document patterns of use and participation. Despite individual differences in style, both participants demonstrated sensitivity to context in their use of language play and an awareness of the ways humor functions as a social practice, subtly adjusting their strategies to changing social situations.